Enhancing Consumer Well-Being and Behavior with Spiritual and Fantasy Advertising. Issue 4 (30th September 2021) - Dodds, Sarah; Jaud, David A.; Melnyk, Valentyna
Abstract: Despite increasing usage of spirituality and fantasy in advertising, especially during the novel coronovirus pandemic, the implications of this trend on consumer well-being and behavior remain unknown. To address this gap, this research conceptualizes a spiritual-fantasy advertising framework and its subsequent effects on consumer well-being and responses to advertising by synthesizing and integrating extant literature on spirituality and fantasy. In contrast to a common view that advertising decreases consumer well-being, we demonstrate how and why advertising evoking spirituality and fantasy can enhance consumers' eudaimonic and hedonic well-being. Our research contributes to a more nuanced understanding of contemporary spirituality that includes fantasy, as well as advertising. We develop a rich research agenda for this important but underexplored area. The proposed comprehensive framework can guide advertising practice and research going forward, especially for those considering such topics as spirituality, fantasy, or consumer well-being.